2008
DOI: 10.1002/jsfa.3401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apple and pear varieties and pH on patulin accumulation by Penicillium expansum

Abstract: BACKGROUND: Accumulation of patulin in apples and pears and subsequently in their by-products is caused mostly by Penicillium expansum which causes blue mould. Fruit pH and other parameters are sometimes characteristic of a certain variety and thus the use of particular varieties might affect patulin content in the final products. The aim of this study was to evaluate the influence of fruit variety and pH on patulin accumulation. Patulin accumulation in both apple and pear juices at different pH and also in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
(29 reference statements)
2
23
0
Order By: Relevance
“…Similarly, Morales et al. () found that the P. expansum growth, estimated in terms of fungal biomass, was unaffected by the fruit juice initial pH.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Morales et al. () found that the P. expansum growth, estimated in terms of fungal biomass, was unaffected by the fruit juice initial pH.…”
Section: Resultsmentioning
confidence: 82%
“…).Moreover, its patulin production capacity has been independently assessed as a function of temperature, pH, and fruit varieties (Morales et al. ; Salomao et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In the assay with BCA formerly referred, time for lesions to expand to 2 cm in control apples was about 30 days and the average patulin accumulated was approx. 200 ng per apple, which is higher than expected, compared to other assays carried out with apples from conventional agriculture (Morales, Barros, Marin, Ramos, & Sanchis, 2008;Morales, Marín, Centelles, et al, 2007). It has been commented formerly (Section 3 regarding use of fungicides) that apples from organic farming presented smaller rots than those from conventional agriculture.…”
Section: Bcas: Effect On Patulin Accumulationmentioning
confidence: 87%
“…reported that apples cold stored during 60 days at CA conditions presented lesions whose diameter ranged from 2 to 4 cm but no patulin was detected. According to other studies (Morales, Marín, Centelles, et al, 2007;Morales, Barros, et al, 2008), patulin accumulation after 60 days of conventional cold storage should range from 44 to 468 ng per apple. Baert et al (2008) reported that temperature influences on the effect of CA storage.…”
Section: Ca Storage: Effect On Apple Decaymentioning
confidence: 97%
“…To prevent patulin occurrence in food, producing moulds should be detected early in the food chain (Barreira, Alvito, & Almeida, 2010;Dvali, Maksimenko, Eller, & Tutel'ian, 1985;Majerus, Hain, & Kölb, 2008;Marín et al, 2011;Morales et al, 2008;Tangni et al, 2003;Yuan, Zhuang, Zhang, & Liu, 2010). The demand is thus to design rapid and sensitive methods that detect these moulds early enough.…”
Section: Introductionmentioning
confidence: 97%